Defeat and Entrapment in Bipolar Disorder: Exploring the Relationship with Suicidal Ideation from a Psychological Theoretical Perspective. Issue 1 (9th March 2017) - Owen, Rebecca; Dempsey, Robert; Jones, Steven; Gooding, Patricia
Abstract : Contemporary psychological theoretical models of suicide hypothesize that defeat and entrapment underlie the development of suicidal ideation. This hypothesis has never been tested in people who experience bipolar disorder. Regression analysis revealed that defeat and entrapment significantly predicted suicidal ideation at 4‐month follow‐up. The relationship between defeat and suicidal ideation was mediated by total entrapment and internal entrapment, but not external entrapment. Results suggest that perceived defeat and entrapment underlie the development of prospective suicidal ideation in bipolar disorder. Findings could potentially improve the assessment of suicide risk in people who experience bipolar disorder.